RTHP-23. HEARING AND FACIAL PRESERVATION FOR VESTIBULAR SCHWANNOMAS TREATED WITH STEREOTACTIC RADIOSURGERY OR FRACTIONATED STEREOTACTIC RADIOTHERAPY. (5th November 2018) - Preet, Komal; Kwan, Isabelle; Udawatta, Methma; Nguyen, Thien; Ong, Vera; Sheppard, John; Duong, Courtney; Gopen, Quinton; Yang, Isaac
Abstract: BACKGROUND: Vestibular schwannomas (VS) are benign intracranial neoplasms arising from the eighth cranial nerve. In recent years, advancing radiological techniques have provided successful non-invasive alternatives for VS therapy. RESEARCH QUESTION: How do the long-term clinical outcomes vary for the three current radiation modalities of stereotactic radiosurgery (SRS), fractionated stereotactic radiotherapy (FSRT), and hypofractionated stereotactic radiotherapy (hypoFSRT)? METHODS: A retrospective chart review was conducted for all patients with unilateral VS at a single academic medical center from 2000 to 2017. Audiograms, physical examinations, and patient-reported symptoms were extracted to assess hearing, facial function and sensation, and statuses of tinnitus, vertigo, and imbalance. RESULTS: Sixty patients were identified (33 FSRT cases, 21 SRS cases, and 6 hypoFSRT cases). Post-operative onset of vertigo and tinnitus demonstrated significant difference between the three modalities (p = 0.035, 0.005). Survival rate analysis revealed the survival time to tinnitus onset also varied significantly when comparing SRS and FSRT (p = 0.050). SIGNIFICANCE: This study aims to elucidate the hearing and facial preservation of the three radiological interventions, thus enabling physicians to optimize patient care.